2008
DOI: 10.1063/1.2901973
|View full text |Cite
|
Sign up to set email alerts
|

Study of the translational diffusion of the benzophenone ketyl radical in comparison with stable molecules in room temperature ionic liquids by transient grating spectroscopy

Abstract: Transient grating (TG) spectroscopy has been applied to the photoinduced hydrogen-abstraction reaction of benzophenone (BP) in various kinds of room temperature ionic liquids (RTILs). After the photoexcitation of BP in RTILs, the formation of a benzophenone ketyl radical (BPK) was confirmed by the transient absorption method, and the TG signal was analyzed to determine the diffusion coefficients of BPK and BP. For comparison, diffusion coefficients of carbon monoxide (CO), diphenylacetylene (DPA), and diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 62 publications
10
66
0
Order By: Relevance
“…The spectra in Bmim-TFSA are consistent with the spectrum recently measured in Bmim-PF 6 by Nishiyama et al 38 Therefore, as previously suggested, 18,19 hydrogen abstraction is slow in TMPA-TFSA.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The spectra in Bmim-TFSA are consistent with the spectrum recently measured in Bmim-PF 6 by Nishiyama et al 38 Therefore, as previously suggested, 18,19 hydrogen abstraction is slow in TMPA-TFSA.…”
Section: Resultssupporting
confidence: 91%
“…However, studies of the reaction of BP(T 1 ) in ILs are limited. 18,19,38 In TMPA-TFSA, the lifetime of BP(T 1 ) is reported to be 19 μs, which is substantially longer than the lifetimes in cyclohexane (300 ns), 2-propanol (5 ns), and benzene (3 μs). 19 In contrast, the lifetime of BP(T 1 ) in Bmim-TFSA has been reported to be 3 μs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…58 Self-diffusion coefficients of photochemically generated CO were reported in both molecular solvents, including alkanes and alcohols, as well as in typical ILs including ͓bmim͔ + cations paired with ͓NTf 2 ͔ − , ͓BF 4 ͔ − and ͓PF 6 ͔ − . 59 Figure 6 plots the self-diffusion of CO following photodissociation. Fractional Stokes-Einstein behavior is observed with the exponent ␣ = 0.68.…”
Section: Viscosity and Transport In Ilsmentioning
confidence: 99%
“…E-mail: ykimura@kuchem.kyoto-u.ac.jp coefficients of these molecules in various RTILs and found that the viscosity dependence of the smaller molecule such as CO is smaller than those of DPCP and DPA. 29 It is interesting to study how the existence of CO2 in RTILs affects the diffusivity of these molecules.…”
Section: Introductionmentioning
confidence: 99%